(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
In the present paper, the contact of area, which is produced between a pair of bodies (flat surface and hemi-cylindrical shape), has been studied under the effect of slippage occurrence, where it represents one of the important problems in the mechanical engineering, especially in robotic design. Many parameters have been studied, like frictional forces, equivalent stresses, friction coefficient, and contact area of deformation. The behavior of these parameters has been monitored during the slippage that is generated between the flat surface made from cast alloy steel and the other part made from rubber. The finite element method (FEM) with SOLIDWORKS software was used to simulate this contact area under the slippage effect. The results of the simulation showed a significant behavior, particularly at the beginning of slippage and the stage of (stick-slip) phenomena, in other words, the simulation outputs indicated that the slippage influence has an important behavior, especially when the phenomena of both slippage and stick-slip stage start to occur. These analyses are intended to understand how the contact area affected to design measures to prevent the slippage occurrence and the damage in contacted bodies.